2006
DOI: 10.1021/bi060309g
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Specificity of MDM2 for the Activation Domains of p53 and p65:  Proline27 Disrupts the MDM2-Binding Motif of p53

Abstract: Transcriptional activation and repression via the transcription factors p53 and p65 are mediated by hydrophobic short linear motifs (FXX phi phi) in their activation domains (ADs). To understand the molecular basis for specificity in binding to disparate biological targets, a series of chimeric peptides was synthesized, with sequences derived from the ADs of p53, which binds both the general transcriptional machinery and the repressor protein MDM2, and p65, which is reported to bind the general transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
102
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(148 citation statements)
references
References 109 publications
(223 reference statements)
23
102
2
1
Order By: Relevance
“…These MD simulations are in agreement with NMR results suggesting that p53 residues 18-26 sample alpha helical conformations [126], as well as with their UV resonance Raman spectroscopy results summarizing the distribution of backbone psi angles in the peptide [125]. Xiong et al also examined the conformational preferences of a P27S mutation in TAD, which is associated with increased binding affinity to MDM2 [127], using MD simulations. They found that the unbound mutant peptide more heavily populates conformations similar to the MDM2-bound conformation of p53, due to increased alpha-helical content.…”
Section: P53 Transcription Activation Domain (Tad)supporting
confidence: 74%
See 1 more Smart Citation
“…These MD simulations are in agreement with NMR results suggesting that p53 residues 18-26 sample alpha helical conformations [126], as well as with their UV resonance Raman spectroscopy results summarizing the distribution of backbone psi angles in the peptide [125]. Xiong et al also examined the conformational preferences of a P27S mutation in TAD, which is associated with increased binding affinity to MDM2 [127], using MD simulations. They found that the unbound mutant peptide more heavily populates conformations similar to the MDM2-bound conformation of p53, due to increased alpha-helical content.…”
Section: P53 Transcription Activation Domain (Tad)supporting
confidence: 74%
“…In this regard, it is always important to compare insights arising from these simulations to data obtained on the complete protein sequence. For example, previous work suggests that stability of the full MDM2-p53 complex is similar to that of the complex formed by a truncated TAD (residues 17-29) peptide [127]. Additionally, the N-terminal domain within the full p53 molecule behaves similarly to the isolated N-terminal residue 1-93 peptide and is not stabilized by contacts with folded regions of p53 [24,133].…”
Section: P53 Transcription Activation Domain (Tad)mentioning
confidence: 94%
“…Zondlo et al recently showed that mutation of the highly conserved Pro-27 in (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) p53 to Ser increased its binding affinity for MDM2 by 50-fold (a decrease in K d from 229 to 4.7 nM) (40). The authors attributed the improvement in MDM2 binding to increased ␣-helicity of the peptide in the complex-a thesis largely confirmed in a molecular dynamic simulation study by Dastidar et al (41).…”
Section: Discussionmentioning
confidence: 92%
“…The role of Asp21 in helping maintain the helix may not be as critical since mutation to Ala does little by way of affecting the interactions of this peptide with MDM2. 17,35 The mouse sequence (Fig. S1B) has a Gly in place of Asp21.…”
Section: Resultsmentioning
confidence: 99%